Jump ship to freedom - Collier, James Lincoln, 1928-; Collier, Christopher, 1930- (New York : Dell, 1987)
In 1787, a fourteen-year-old slave, anxious to buy freedom for himself and his mother, escapes from his dishonest master and tries to find help in cashing the soldier's notes received by his father for fighting in the Revolution.
"A Yearling book."
Junior High School Library Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
5.4
5-8
Keywords: Slavery -- Fiction; Afro-Americans -- Fiction; Slavery -- United States -- Fiction; Blacks -- Fiction